Genome-wide association study identifies genes for biomarkers of cardiovascular disease: serum urate and dyslipidemia. - Wallace, C; Newhouse, S; Braund, P; Zhang, F; Tobin, M; Falchi, M; Ahmadi, K; Dobson, R; Marçano, A; Hajat, C; Burton, P; Deloukas, P; et al. (2008)
Many common diseases are accompanied by disturbances in biochemical traits. Identifying the genetic determinants could provide novel insights into disease mechanisms and reveal avenues for developing new therapies. Here, we report a genome-wide association analysis for commonly measured serum and urine biochemical traits. As part of the WTCCC, 500,000 SNPs genome wide were genotyped in 1955 hypertensive individuals characterized for 25 serum and urine biochemical traits. For each trait, we assessed association with individual SNPs, adjusting for age, sex, and BMI. Lipid measurements were further examined in a meta-analysis of genome-wide data from a type 2 diabetes scan. The most promising associations were examined in two epidemiological cohorts. We discovered association between serum urate and SLC2A9, a glucose transporter (p = 2 x 10(-15)) and confirmed this in two independent cohorts, GRAPHIC study (p = 9 x 10(-15)) and TwinsUK (p = 8 x 10(-19)). The odds ratio for hyperuricaemia (defined as urate >0.4 mMol/l) is 1.89 (95% CI = 1.36-2.61) per copy of common allele. We also replicated many genes previously associated with serum lipids and found previously recognized association between LDL levels and SNPs close to genes encoding PSRC1 and CELSR2 (p = 1 x 10(-7)). The common allele was associated with a 6% increase in nonfasting serum LDL. This region showed increased association in the meta-analysis (p = 4 x 10(-14)). This finding provides a potential biological mechanism for the recent association of this same allele of the same SNP with increased risk of coronary disease.